(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2018)
To characterize the state of the art in the training of cognitive-behavioral therapists, peer reviewed papers indexed in the PsycNet database, between the years 2011 and 2016, were evaluated in terms of the themes of the publication, the training strategies and the measures of competence employed. The scientific production on the training of cognitive-behavioral therapists is scarce (N = 24). Five themes were identified: Training Modalities, Training to work in Specific Clinical Conditions, Training to work with Specific Clients, Personal Development of the Therapist and Training for the Domain of Techniques or Specific Models. The most used training strategies were supervision and expanded training, evaluation occurred predominantly with the examination of the therapist’s practice. Since it is a clinical approach that has been highly efficient, procedures to evaluate the training of the cognitive-behavioral therapist and, more specifically, the acquisition and evaluation of competencies are suggested.